Rise and decline of the coffee industry in 19th-century Batangas causes and consequences - Belamide, Aidel Paul G. (Philippine Social Sciences Review, 2020)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/9896/8729